Use the method of parsing anomalous valueIn estimating the character parameter - كوركيس, حازم منصور (Journal of Economics and Administrative Sciences, 2009)
In this paper the method of singular value decomposition  is used to estimate the ridge parameter of ridge regression estimator which is an alternative to ordinary least squares estimator when the general linear regression model suffer from near multicollinearity.